Mental Health in John Green’s Turtles All the Way Down - Juan Abdullah Ibrahim; Khadeeja Saeed Ismail (Zanco Journal of Humanity Sciences)
Mental health and illness have been tackled and theorized over centuries in various cultures. Mental health possesses a complex history in being used for various causes and perceptions due to the needs of a certain group of people. Characters who develop mental illness, in classic novels, usually go crazy, or they are neglected, they die and things turn to be well for the other sane characters, or even they commit suicide. The trope of dismissing characters with mental health issues is unnerving in classic literature. Thereby, it was not possible for characters suffering from mental illness to be any type of hero since they were frequently killed off or called villainous.